Dinamika Menuju Hadirnya Calon Tunggal Pada Pilkada Kabupaten Bone Tahun 2020 - Muhammad Zaky Irgiawan; Haryanto Haryanto (Politik Islam, 2023)
This paper aims to show the dynamics in determining the candidate for political party support in the 2018 Bone Regency Regional election (Pilkada). In the 2018 Regional Electon, Bone Regency was presented only one pair of candidate where became the only candidate in that regional election. The candidate were Andi Fahsar M. Padjalangi and Ambo Dalle. In the end, this pair won by getting 232,955 votes or 63.05%. The presence of a single candidate in the 2018 regional election after the previous election in 2013 that was attended by 6 pair of candidates certainly raises questions related to how the dynamics of political parties ultimately to promote same candidate. Through qualitative research method used was in the research for this paper, it describe the dynamics of the political parties. The results of this study indicate that there are dynamics that occur. - each political party. Whereas in the external dynamics, it can be seen from the relationship between political parties that are not running effectively and the relationship between the single candidate with supporting party which has good relationship to the top officials of the supporting party where brings benefits for both parties to achieve the interests them.